Reduced Long‐Term Risk of Aortic Aneurysm and Aortic Dissection Among Individuals With Type 2 Diabetes Mellitus: A Nationwide Observational Study. Issue 3 (24th January 2018) - Avdic, Tarik; Franzén, Stefan; Zarrouk, Moncef; Acosta, Stefan; Nilsson, Peter; Gottsäter, Anders; Svensson, Ann‐Marie; Gudbjörnsdottir, Soffia; Eliasson, Björn
Abstract : Background: No studies have examined long‐term risks for aortic aneurysm (AA) and aortic dissection (AD) or mortality after AA or AD hospitalization among patients with type 2 diabetes mellitus (T2DM). Methods and Results: In this observational cohort study, we linked data for patients with T2DM in the Swedish National Diabetes Register, and 5 individually matched population‐based control subjects (CSs) without diabetes mellitus (on the basis of sex, age, and county), to other national databases to capture hospitalizations and death. We examined the risk of hospitalization for AA and AD, as well as mortality risk after AA and AD using Kaplan‐Meier curves and Cox regression hazards models. Data on 448 319 patients with T2DM and 2 251 015 CSs were obtained between 1998 and 2015. Mean follow‐up time was 7.0 years for the T2DM group and 7.2 years for the CS group. Patients with T2DM had a relative risk reduction of 28% (hazard ratio, 0.72; 95% confidence interval, 0.68–0.76; P <0.0001) for AA and a 47% relative risk reduction (hazard ratio, 0.53; 95% confidence interval, 0.42–0.65; P <0.0001) for AD compared with CSs. Patients with T2DM had a relative risk reduction of 12% (hazard ratio, 0.88; 95% confidence interval, 0.82–0.94; P <0.0001) for mortality after hospitalization for AA, and unaltered risk (hazard ratio, 1.07; 95% confidence interval, 0.85–1.34; P =0.5859) for mortality after AD, up to 2 years compared with CSs. Conclusions: Patients with T2DM had significantly reduced risks of AA and AD as well as reduced risk of mortality after hospitalization for AA, compared to CS. Data suggest that glycated cross‐links in aortic tissue may play a protective role in the progression of aortic diseases among patients with T2DM.